2022
DOI: 10.3389/fnut.2022.909283
|View full text |Cite
|
Sign up to set email alerts
|

Production of Prebiotic Xylooligosaccharides via Dilute Maleic Acid-Mediated Xylan Hydrolysis Using an RSM-Model-Based Optimization Strategy

Abstract: Xylooligosaccharides (XOS) are functional feed additives that are attracting growing commercial interest owing to their excellent ability to modulate the composition of the gut microbiota. The acid hydrolysis-based processing of xylan-containing materials has been proposed to represent a cost-effective approach to XOS preparation, with organic acids being preferable in this context. As such, in the present study, maleic acid was selected as a mild, edible organic acid for use in the hydrolysis of xylan to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Therefore, too high values of both the two variables would lead to a decline in XOS yield and an increase in xylose yield. This phenomenon is in good agreement with the previous literature ( 23 ). Additionally, similar observations also could be observed in Figures 3B , C , which revealed the interaction effects of reaction temperature and hydrolysis period, as well as GluA concentration and hydrolysis period on XOS yield.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, too high values of both the two variables would lead to a decline in XOS yield and an increase in xylose yield. This phenomenon is in good agreement with the previous literature ( 23 ). Additionally, similar observations also could be observed in Figures 3B , C , which revealed the interaction effects of reaction temperature and hydrolysis period, as well as GluA concentration and hydrolysis period on XOS yield.…”
Section: Resultssupporting
confidence: 94%
“…Different from mineral acids, organic acids are generally weak acids and have desirable features of less equipment corrosiveness and fewer byproducts, which are more preferable for producing XOS with a higher yield (17, 21). Theoretically, organic acids, such as gluconic acid, maleic acid, citric acid and xylonic acid, could be directly co-prepared with XOS and applied as feed additives (17, 19,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Guillon et al found that succinate could reduce the upregulation of inflammatory factors and metabolic disorders of various physiological processes caused by the influenza A virus [ 27 ]. Maleic acid can release H + to promote the hydrolysis of hemicellulose [ 28 ]. In this study, spermidine promoted the upregulation of succinate and maleic acid, and it was speculated that spermidine has anti-inflammatory effects and promotes digestion.…”
Section: Discussionmentioning
confidence: 99%